THERE IS NO CORRELATION BETWEEN STAGES OF NAFLD ASSESSED BY LIVER BIOPSY AND THE DIAGNOSTIC CRITERIA FOR SARCOPENIA IN ACTIVE POPULATIONS: A CROSS-SECTIONAL STUDY - Ferreira, Luis Fernando; Berleze, Kally Janaina; D´Ávila, André Ferreira; Tovo, Cristiane Valle; da Rosa, Luis Henrique Telles (Arquivos de Ciências da Saúde da UNIPAR, 2023)
Objective: To demonstrate the correlations of the diagnostic criteria for sarcopenia and the levels of Non-alcoholic Fat Liver Disease (NAFLD) assessed by liver biopsy in a physically active population. Methods: Cross-sectional study. Individuals aged >18 years, with NAFLD confirmed by liver biopsy, physically active. Sarcopenia assessment followed EWGSOP2: muscle strength by handgrip, Skeletal Muscle Mass by Bioimpedance, and physical performance by usual gait speed. Statistical Analysis: To test differences between groups in continuous variables, Student's T or Mann-Whitney U Test for independent samples. Pearson and Spearman tests were used for correlations. A 5% significance was considered (p<0.05). Results: 52 patients with NAFLD included, consisting of 35 women and 15 men. There was no difference in age or anthropometric variables. Were found difference statically significant in platelets (higher in women), basal insulin, HOMA-IR and Quick (higher in men). In sarcopenia, the handgrip strength showed difference in favors of men. There was no statistically significant correlation between the sarcopenia and NAFLD levels. Discussion: sarcopenia has been reported as an independent risk factor for NAFLD and its progressions. The physical exercise is one of the most recommended and more effective treatment for both conditions, so is expected that a non-sedentary individual can reduce both indicators. However, there is no consensus about the best method. Also, the both conditions share heterogeneity in diagnosis, prognosis, reason for develop and risk factors across the literature. Conclusion: For populations where most individuals are physically active, it is not possible to find correlation between sarcopenia diagnostic criteria and the stages of NAFLD.